Cover Picture: Prediction of subsequent osteoporotic vertebral compression fracture on CT radiography via deep learning (View 6/2022). Issue 6 (19th December 2022) - Hu, Xiao; Zhu, Yanjing; Qian, Yadong; Huang, Ruiqi; Yin, Shuai; Zeng, Zhili; Xie, Ning; Ma, Bin; Yu, Yan; Zhao, Qing; Wu, Zhourui; Wang, Jianjie; et al.
Abstract : The cover image describes the prediction model based on deep learning, which could analyze characteristics of patients with twice osteoporotic vertebral compression fracture (OVCF), predicts subsequent OVCF in using computed tomography (CT) images. The model offers an advanced method to predict subsequent OVCF with high precision, low false positives and simple operation, which could be used to screen high‐risk groups of osteoporotic vertebral fracture.